2008
DOI: 10.1152/ajprenal.90374.2008
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced renal sensitivity of the spontaneously hypertensive rat to urotensin II

Abstract: Abdel-Razik AE, Balment RJ, Ashton N. Enhanced renal sensitivity of the spontaneously hypertensive rat to urotensin II. Am J Physiol Renal Physiol 295: F1239 -F1247, 2008. First published August 13, 2008 doi:10.1152/ajprenal.90374.2008.-Urotensin II (UII) has been implicated widely in cardiovascular disease. The mechanism(s) through which it contributes to elevated blood pressure is unknown, but its emerging role as a regulator of mammalian renal function suggests that the kidney might be involved. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 34 publications
4
21
1
Order By: Relevance
“…However, in this study, after multiple-dose treatment with palosuran, we were not able to detect an effect on plasma U-II levels and urinary excretion parameters. Several reports in animals suggest that U-II has an important role in the occurrence of renal fibrosis and dysfunction [40,41], which is substantiated by the fact that U-II is produced in the kidney [42]. As the (patho)physiological pathway of U-II has not been fully characterized in patients or healthy subjects, differences in physiology could explain the absence of effect in healthy subjects in this study.…”
Section: Discussionsupporting
confidence: 55%
“…However, in this study, after multiple-dose treatment with palosuran, we were not able to detect an effect on plasma U-II levels and urinary excretion parameters. Several reports in animals suggest that U-II has an important role in the occurrence of renal fibrosis and dysfunction [40,41], which is substantiated by the fact that U-II is produced in the kidney [42]. As the (patho)physiological pathway of U-II has not been fully characterized in patients or healthy subjects, differences in physiology could explain the absence of effect in healthy subjects in this study.…”
Section: Discussionsupporting
confidence: 55%
“…However, the physiological role of UII in the kidney remains controversial with studies reporting attenuation and elevation of important renal parameters, including total renal blood flow (RBF), glomerular filtration rate (GFR), urine flow rate (UV), and urinary sodium (U Na V) and potassium (U K V) excretion (Zhang et al 2003, Ovcharenko et al 2006, Song et al 2006, Abdel-Razik et al 2008a,b, Shi et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 These experiments showed that urantide increased GFR, urine output and urinary sodium excretion in both strains. 18,19 In addition, these investigators found that infusion of rat U-II reduced RBF, GFR, urine output and urinary sodium excretion, and that these effects were blocked by urantide. 18,19 Taken together, these results show that endogenous U-II exerts a tonic vasoconstrictor influence on the renal vasculature in rats.…”
Section: Introductionmentioning
confidence: 89%
“…17 In the rat kidney, U-II has been shown to cause both renal vasoconstriction and vasodilation. 10,14,[18][19][20] The effects of endogenous U-II on renal function has been examined with the selective UT receptor antagonist, urantide, both in normotensive rat strains (Sprague-Dawley) and in spontaneously hypertensive rats (SHR). 18,19 These experiments showed that urantide increased GFR, urine output and urinary sodium excretion in both strains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation